The difficulties of the elementary school students in solving the mathematical narrative test items - Dwi Widyastuti Nurharyanto; Heri Retnawati (Jurnal Prima Edukasia, 2020)
Mathematical learning is based on the context of everyday life and is reflected in the evaluation questions given to students. One type of question that is proper for the teacher to use is a word problem. Word problems are more difficult than other models. This type does not present problems with mathematical models directly but with narrative stories that students should understand first. This research was phenomenological research that aimed to find out what difficulties were experienced by students in solving mathematical problems presented narratively. The participants of this study were 121 fifth grade students from five elementary schools in the Special Region of Yogyakarta, Indonesia. Student errors were analyzed using the Newman Analysis Method. The Newman Analysis Method grouped students' mistakes into five categories: reading errors, comprehension errors, transformation errors, process skills, and encoding errors. The results of this study indicate that students have comprehension errors were 44.04%, transformation errors were 40.22%, process skills errors were 57.44%, and encoding errors were 57, 44%. Most errors are in problem number three with the type of reading errors. One of the reasons is the ability of students who are still lacking to understand can cause problems at a later stage.